IMPLEMENTASI PEMBANGUNAN KEPARIWISATAAN KABUPATEN BANYUWANGI: Studi Kasus Kawasan Taman Wisata Alam Kawah Ijen - Bayu Krisna Ardiansyah; Rizari Rizari; Hendrawati Hamid (Fakultas Politik Pemerintahan IPDN, 2020)
This article is a follow-up study from Irawan's research in 2015 about the Implementation of Tourism Development Policy which discusses all of tourist objects in Banyuwangi. It become the main focus of tourist destinations in the Banyuwangi Tourism Development Master Plan, but infrastructure and marketing of the Kawah Ijen Nature Park have not been priority. This study aims to find out how the Implementation of Tourism Development Policy in the Kawah Ijen Nature Park Banyuwangi. Researchers used research methods with qualitative methods with a post-positivist approach. The author sharpens the object of study only at the research object in Kawah Ijen Nature Park, annalize with different perspective from previous study, namely the content of policy and the context of implementation as determinant indicator of public policy outcomes. The results are the high types of benefits for community, the degree of change looks good and has increased human resources. Although compliance and responsiveness in implementing policies are still weak due to lack of communication between policymakers and implementers. The conclusion shows the implementation of tourism development policy in Kawah Ijen Nature Park has been going well enough. The suggestion to improve policy implementation, by collaborate all of elements of policy implementers, the private sector and the community. Keywords: Policy Implementation, Tourism Development, Kawah Ijen Nature Park